2005
DOI: 10.1159/000089058
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Balloon Valvuloplasty in a Fetus with Critical Pulmonary Stenosis/Atresia with Intact Ventricular Septum and Heart Failure

Abstract: Outcome of fetuses with critical pulmonary stenosis (critical PS) or atresia of the pulmonary valve (PA) with intact ventricular septum (IVS) is closely related with right ventricle hypoplasia and its consequent hemodynamics. Fetal echocardiography not only allows early detection of this condition but also monitors its normally unfavorable evolution. These cases may benefit from intrauterine intervention relieving outflow tract obstruction in order to achieve a biventricular circulation. Successful valvuloplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(42 citation statements)
references
References 32 publications
0
40
0
2
Order By: Relevance
“…Therefore, prenatal treatment could be a unique opportunity to take advantage of a better ventricular growth than that achievable postnatally. A few case reports and small case series have shown that fetal pulmonary valvuloplasty is technically feasible and associated with continued growth of RV structures8, 9, 10, 11, 12, 13. The International Fetal Cardiac Intervention Registry reported 16 fetal pulmonary valvuloplasties, of which 11 procedures were successful and resulted in seven liveborn patients, five of which were discharged with a biventricular circulation.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, prenatal treatment could be a unique opportunity to take advantage of a better ventricular growth than that achievable postnatally. A few case reports and small case series have shown that fetal pulmonary valvuloplasty is technically feasible and associated with continued growth of RV structures8, 9, 10, 11, 12, 13. The International Fetal Cardiac Intervention Registry reported 16 fetal pulmonary valvuloplasties, of which 11 procedures were successful and resulted in seven liveborn patients, five of which were discharged with a biventricular circulation.…”
Section: Introductionmentioning
confidence: 99%
“…48 It was available for fetal arrhythmias, fetal heart failure, and in some cases for very few structural CHD. 15,39 The majority of neonates who have CHD will not require delivery room resuscitation in excess of routine care. 22 However, resuscitation could be required in a small number of prenatally diagnosed CHD including transposition of the great arteries with intact ventricular and restrictive atrial septum, hypoplastic left heart syndrome with intact atrial septum, obstructed total anomalous pulmonary venous return, and complete congenital heart bloc.…”
Section: What After the Prenatal Diagnosis Of Fetal Cardiac Lesion?mentioning
confidence: 99%
“…52 The survival after fetal aortic and pulmonary balloon valvuloplasty has been reported, and seemed very encouraging approach to the treatment of the fetal CHD. 15,53 The world discouraging experience of percutaneous ultrasound-guided balloon valvuloplasty in human fetuses with severe aortic valve obstruction was reported in 12 fetuses between 27th and 33rd weeks of gestation. 54 The range between initial presentation and intervention was 3 days to 9 weeks.…”
Section: What After the Prenatal Diagnosis Of Fetal Cardiac Lesion?mentioning
confidence: 99%
See 2 more Smart Citations